Trinidad. Cocoa trees in full bearing - (:unkn) unknown (My University, 2010)
A picture of a cocoa tree full of its fruit ready for harvest.
Colour: Coloured; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cocoa; Agriculture; Theobroma cocoa